Occurrence of head lice in children and adolescents seen at a hospital in Uberlândia, central Brazil - Rubia Silva Cadima, Leticia; Borges-Moroni, Raquel; Mendes, Julio; Tonissi Moroni, Fabio (Revista de Patologia Tropical / Journal of Tropical Pathology, 2021)
The purpose of this study was to verify the occurrence of head lice in children at a public hospital in Uberlândia, MG and factors associated with pediculosis such as sex, age, hair characteristics and socioeconomic conditions, as well as obtaining information from their parents/guardians regarding the epidemiology, its transmission, prevention and control. To obtain the data, direct hair inspection and a characterization sheet and questionnaire were utilized. An occurrence rate of 6.1 % was found in 230 children examined in a public hospital, 111 females and 119 males with the highest rates observed in female children aged 4-8 with medium to long hair. Income, level of education, hair washing, hair type, color and thickness did not seem to influence the distribution of pediculosis in the children seen in the hospital in Uberlândia. The questionnaire answered by parents/guardians indicated that the children had had at least one infestation in their lifetime. The use of fine comb and pesticides were the most usual control methods adopted. The most frequent symptom was severe itching on the scalp. Although the occurrence of head pediculosis is declining, it is still a prevalent public health problem in the child population of Uberlândia, MG. Pediculosis may be associated with sex, age and hair characteristics. Variations in the degree of these influencing factors depend on the profile of the population studied. Additional studies are required in population groups over time, particularly in those that are inadequately assisted or lack state education and health assistance. KEY WORDS: Pediculosis; ocurrence; Minas Gerais; Brazil.